Evaluation of Anemia among Lactating Mothers and their Children Under Two Years of Age - ahmed, Huda (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The aim of this study is to evaluate anemia among lactating women and their children less than 2 years of age. Methodology: The study was done on (148) lactating mothers and their children under 2 years of age in the primary health care center at AL-Salam Quarter/Baghdad from l/10/2009 to 15/10/2010. Result: This study recommends that there is a significant relationship between anemic mothers and their children. The study also revealed that there is (77.8%) from nursing mothers in the age groups (25-29) who suffered from anemia, while (23.1%) for the age group (20-24) did not have anemia Recommendation: We encourage the use of breast milk or iron-fortified infant formula only for any milk-based part of the diet (e.g., in infant cereal) and discourage the use of low-iron milks (e.g., cow’s milk, goat’s milk, and soy milk) until age 12 months.